JARINGAN ULAMA NUSANTARA: PERAN INTELEKTUAL DALAM MEMBENTUK PERADABAN MELAYU-ISLAM - Niswah, Choirun; Putra, Aldo; Anggraina, Rina; Rahmadani, Angel (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Islam in the Indonesian archipelago emerged as a transformative force that not only touched on spiritual aspects but also profoundly reconstructed the social and intellectual structures of society. This research focuses on the strategic role of the Indonesian ulama network as a key intellectual agent in shaping the foundations of a distinctive Malay-Islamic civilization. Using a qualitative approach with descriptive-analytical literature study methods, this study examines historical literature on the dynamics of ulama thought and the transmission of knowledge. The study's findings indicate that ulama acted not only as propagators of religion but also as cultural mediators, integrating universal Islamic values ??with local wisdom through a harmonious process of acculturation. This network also played a vital role in standardizing the Malay language as a lingua franca for scholarship and establishing basic educational institutions such as Islamic boarding schools (pesantren), which became pillars of the modernization of the Muslim community. The main conclusion emphasizes that this intellectual synergy has given birth to a unique, moderate, and adaptive Malay-Islamic civilizational identity, in which ulama successfully bridged global and local traditions, thus strengthening the existence of Islam as a central element in the history of Southeast Asian civilization. ABSTRAKIslam di kawasan Nusantara hadir sebagai kekuatan transformatif yang tidak hanya menyentuh aspek spiritual, tetapi juga merekonstruksi struktur sosial dan intelektual masyarakat secara mendalam. Penelitian ini memfokuskan kajian pada peran strategis jaringan ulama Nusantara sebagai agen intelektual kunci dalam membentuk fondasi peradaban Melayu-Islam yang distingtif. Menggunakan pendekatan kualitatif dengan metode studi kepustakaan yang bersifat deskriptif-analitis, penelitian ini menelaah literatur historis mengenai dinamika pemikiran dan transmisi keilmuan ulama. Temuan studi menunjukkan bahwa para ulama tidak hanya bertindak sebagai penyebar agama, tetapi juga sebagai mediator kultural yang mengintegrasikan nilai-nilai Islam universal dengan kearifan lokal melalui proses akulturasi yang harmonis. Jaringan ini juga berperan vital dalam membakukan bahasa Melayu sebagai lingua franca keilmuan serta mendirikan lembaga pendidikan basis seperti pesantren yang menjadi pilar modernisasi umat. Simpulan utama menegaskan bahwa sinergi intelektual ini telah melahirkan identitas peradaban Melayu-Islam yang unik, moderat, dan adaptif, di mana ulama berhasil menjembatani tradisi global dan lokal, sehingga memperkokoh eksistensi Islam sebagai elemen sentral dalam sejarah peradaban Asia Tenggara.